Micro-abrasion-corrosion Maps of 316L Stainless Steel in Artificial Saliva - Hayes,A; Sharifi,S; Stack,MM (Journal of Bio and Tribo Corrosion, 2015)
The role of salivary media is essential during mastication and ingestion processes; yet it can hinder the performance of foreign materials in the oral cavity. The aim of this study was to examine the effects of applied load and applied electrical potential on the tribo-corrosion mechanisms of 316L stainless steel in an environment similar to oral cavity conditions. 316L stainless steel is a material commonly used in dentistry for orthodontic braces, wires and in some cases as dental crowns. This is due to its favourable corrosion resistance. Relatively few studies have examined the materials performance in an oral environment. The results of this work were used to generate polarisation curves and wastage and mechanism maps to describe the material’s tribo-corrosion behaviour. A significant difference in corrosion current densities was observed in the presence of abrasive particles suggesting the removal of the protective chromium oxide passive film. It was found that the corrosion resistant nature of 316L stainless steel resulted in a wear mechanism which was micro-abrasion dominated for all test conditions.